Sales Performance dan Faktor yang Mempengaruhinya - Ayu Magdalena; Praptini Yulianti; Muh. Asrori Afandi (UMSurabaya Publishing, 2021)
This study aims to determine the effect of organizational justice, intrafirm competition, and salesperson organization fit on salesperson deviance workplace behavior and their impact on sales performance. This study uses a quantitative approach, with the method of collecting data through a questionnaire. The number of samples in this study was 108 employees. The analysis technique used is Partial Least Square (PLS). This study indicates that (1) organizational justice and intrafirm competition have a negative and significant effect on deviance workplace behavior. (2) intrafirm competition has a positive and significant effect on deviance workplace behavior. (3) salesperson organization fit has a negative and insignificant effect on deviance workplace behavior. (4) deviance workplace behavior has a negative and significant effect on the sales performance of sales force employees in the banking industry.Keywords : Deviance Workplace Behavior; Intrafirm Competition; Organizational Justice; Salesperson Organization Fit; Sales PerformanceCorrespondence to : ayu.magdalena@gmail.com Penelitian ini bertujuan untuk mengetahui pengaruh organizational justice, intrafirm competition dan salesperson organization fit terhadap salesperson deviance workplace behaviour dan dampaknya terhadap sales performance. Penelitian ini menggunakan pendekatan kuantitatif, dengan metode pengumpulan data melalui kuesioner. Jumlah Sampel dalam penelitian ini 108 karyawan. Teknik analisis yang digunakan adalah Partial Least Square (PLS). Hasil dari penelitian ini menunjukkan bahwa (1) organizational justice dan intrafirm competition berpengaruh negatif dan signifikan terhadap deviance workplace behavior. (2) intrafirm competition berpengaruh positif dan signifikan terhadap deviance workplace behavior. (3) salesperson organization fit berpengaruh negatif dan tidak signifikan terhadap deviance workplace behavior. (4) deviance workplace behavior berpengaruh negatif dan signifikan terhadap sales performance pada karyawan tenaga penjualan yang ada di industri perbankan.Kata Kunci : Deviance Workplace Behavior; Intrafirm Competition; Organizational Justice; Salesperson Organization Fit; Sales Performance